The Role of Systematic Reviews in Hematological Diseases Treatment - Kartika, Juspeni; Legiran, Legiran (Universitas Brawijaya, 2024)
Evidence-based medicine utilizes medical literature to guide clinical decisions, diagnose and treat patients. Practitioners use evidence-based guidelines to support or oppose a medical intervention. Therefore, systematic reviews of high-quality randomized controlled trials are the highest quality reviews, as these investigations are at the top of the hierarchy of evidence-based medicine. In continuing medical education, systematic reviews are used to inform medical interventions that should be used or avoided in order to protect patient safety and improve health services based on evidence5. In addition, systematic reviews produce empirical and focused answers. Regarding the explanation above, the author would like to explain further regarding the role of systematic reviews in therapeutic approaches in the field of hematology.